Harnessing rhizospheric core microbiomes from arid regions for enhancing date palm resilience to climate change effects - Ben Zineb, Ameni; Lamine, Mariem; Khallef, Ahlem; Hamdi, Helmi; Ahmed, Talaat; Al-Jabri, Hareb; Alsafran, Mohammed; Mliki, Ahmed; Sayadi, Sami; Gargouri, Mahmoud (Frontiers in Microbiology, 2024)
Date palm cultivation has thrived in the Gulf Cooperation Council region since ancient times where it represents a vital sector in agricultural and socio-economic development. However, climate change conditions prevailing for decade in this area, next to rarefication of rain, hot temperatures, intense evapotranspiration, rise of sea level, salinization of groundwater, and intensification of cultivation contributed to increase salinity in soil as well as in irrigation water, and to seriously threaten date palm cultivation sustainability. There are also growing concerns about soil erosion and its repercussions on date palm oases. While several reviews reported on solutions to sustain date productivity, including genetic selection of suitable cultivars for the local harsh environmental conditions and the implementation of efficient management practices, no systematic review on the desertic plants below-ground microbial communities and their potential contributions to date palm adaptation to climate change has been reported yet. Indeed, desert microorganisms are expected to address critical agricultural challenges and economic issues. Therefore, the primary objectives of the present critical review is to (1) analyze and synthesize current knowledge and scientific advances on desert-plants associated microorganisms, (2) review and summarize the impacts of their application on date palm, and (3) identify possible gaps and suggest relevant guidance for desert plants microbes’ inoculation approach to sustain date palm cultivation within the Gulf Cooperation Council in general and in Qatar in particular.